Instrumental compression force and meat attribute changes in woody broiler breast fillets during short-term storage. (22nd June 2018) - Sun, X; Koltes, D A; Coon, C N; Chen, K; Owens, C M
ABSTRACT: Woody breast (WB) is a myopathy of the Pectoralis major muscle in broilers that is characterized by increased hardness of the raw fillet. This defect increases economic losses due to associated decreased meat quality and the addition of training skilled laborers to identify problematic fillets. Therefore, the objectives of this study were to determine if compression force (CF) could be used as a non-invasive method of detecting WB and to assess changes in meat attributes during cold storage. Deboned fillets (n = 121) were collected from 8-wk-old broilers, and categorized as normal (NORM, n = 42), mild (MILD, n = 39), and moderate/severe (SEV, n = 40) for WB. Right fillet weight, drip loss, and CF of the cranial region were measured on the day of processing (day 0) and 1, 2, 3, 4, and 8 d of cold storage (4°C). Left fillets were sampled for sarcomere length (SL) and gravimetric fragmentation index (GFI) analysis following 1, 3, and 8 d of cold storage. Initial breast fillet weight, CF, cumulative drip loss, and SL increased as severity of WB category increased ( P < 0.05). Compression force was highly correlated to WB severity ( r s = 0.79). Compression force, SL, and GFI declined with storage time ( P < 0.05), whereas cumulative drip loss increased ( P <0.05). Cumulative drip loss, SL, and GFI had interactions between storage length and WB category ( P < 0.05), where SEV generally changed more than NORM over time. The results of this study indicate that increased severity of WB fillets is associated with higher CF compared to normal fillets. Furthermore, there is a softening effect of the meat over time and data suggest that moisture (drip loss) and myofibril proteolysis (fragmentation) contribute to these changes. Using instrumental CF to assess fillet hardness can be used as a reliable tool to identify WB. However, adaptability in the commercial processing require additional studies prior to the incorporation into the processing plant for online grading purposes.